2019
DOI: 10.1111/jdv.15608
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctivitis in atopic dermatitis patients with and without dupilumab therapy – international eczema council survey and opinion

Abstract: Background Conjunctivitis is common in patients with atopic dermatitis ( AD ) in general and a commonly reported adverse event in AD clinical trials with dupilumab. Objective To survey opinions and experience about conjunctivitis occurring in AD , including those during dupilumab treatment in a group of AD experts from the International Eczema Council ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
73
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 28 publications
3
73
0
1
Order By: Relevance
“…Dupilumab, trade name Dupixent (Sanofi and Regeneron Pharmaceuticals), is a monoclonal antibody that acts as an interleukin-4 (IL-4) receptor alpha antagonist that blocks the signaling of IL-4 and IL-13. 1,2 It is increasingly being used clinically to control over expression of such Th2 cytokines found in a variety of allergic diseases. 3,4 Dupilumab was first approved by the US Food and Drug Administration for eczema in March 2017 followed by approval for moderate to severe asthma in October 2018.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dupilumab, trade name Dupixent (Sanofi and Regeneron Pharmaceuticals), is a monoclonal antibody that acts as an interleukin-4 (IL-4) receptor alpha antagonist that blocks the signaling of IL-4 and IL-13. 1,2 It is increasingly being used clinically to control over expression of such Th2 cytokines found in a variety of allergic diseases. 3,4 Dupilumab was first approved by the US Food and Drug Administration for eczema in March 2017 followed by approval for moderate to severe asthma in October 2018.…”
Section: Introductionmentioning
confidence: 99%
“…5 Similar approval has been achieved outside the United States, with the European Medicine Agency authorizing dupilumab for AD September 2017 with numerous other approval under way. 1,6,7 Throughout the various trials for approval of dupilumab, conjunctivitis has been identified. In various phase 3 clinical trials, patients with AD treated with dupilumab had a 14% to 19% rate of conjunctivitis, whereas patients with AD treated with a placebo had an 8% rate of conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An expert consensus gives recommendations how to deal with this problem in clinical practice (Thyssen et al in this issue). 1 Independent from any kind of treatment, often people with 'sensitive skin' also complain about ocular problems. The nature of 'sensitive eyes' is not well defined.…”
mentioning
confidence: 99%